Harvest in the Snow : My Crusade to Rescue the Lost Children of Bosnia - Blackman, Ellen (Book collections on Project MUSE., 2014)
At the height of the Serbian siege of Sarajevo, Ellen Blackman could no longer bear the televised images of wounded children desperate for medical care. So she set off for Bosnia. There she shared the tragedies and occasional triumphs of a brave people whose world was crumbling around them while a seemingly indifferent world stood by. And despite tremendous bureaucratic and dangerous obstacles, she got the children out.